DIDAKTIS PADA LEGENDA ASAL USUL SUNGAI LANDAK DI KALIMANTAN BARAT - Meisandra, Meisandra; Cindy Vanesa Marsadu; Joya, Joya; Luky Juniarti; Saptiana Sulastri; Dini Hajjafiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and describe the didactic values contained in the legend of the origin of the Landak River in West Kalimantan. The method used is qualitative descriptive research employing a content analysis approach to the folklore text. The data were analyzed through a process of reduction, categorization, and interpretation to identify the educational values contained in the story. The results of the study indicate that the legend contains moral, social, responsibility, patience, religious, and local wisdom values that play a role in shaping the character of the community. These values remain relevant in modern life, particularly in the character education of the younger generation.